(untitled) (UCC Student Medical Journal, 2024)
In the blink of an eye I was on my flight home, wondering how two months, which felt like two years, could pass as quickly as two weeks. During the summer of 2022 I was lucky enough to be one of the three DEM3/GEM2 students to participate in an erasmus exchange in Madrid, Spain. This was the first year this programme was launched and I was one very happy ‘guinea pig’. There’s not a day that goes by where I don’t wish I could be back in La Latina, in the heart of Madrid, basking in the scorching heat. Although, on that note, the scorching heat I could do without…